Sensitivity of forest water balance and physiological drought predictions to soil and vegetation parameters – A model-based study. (April 2018) - Speich, Matthias J.R.; Zappa, Massimiliano; Lischke, Heike
Abstract: A global sensitivity analysis was conducted on a dynamic water balance model with 19 parameters describing canopy structure, stomatal regulation and soil characteristics, to quantify the importance of vegetation and soil properties in coupled models of hydrology and forest dynamics. Main outputs were total evaporation, as well as a physiological drought index calculated from actual and potential transpiration. Parameter sensitivity was assessed at ten temperate to sub-alpine locations, covering both water-limited and energy-limited sites. Varying parameter values within plausible ranges led to differences of several hundreds of mm/year in predicted long-term evaporation. Root zone storage is the most important parameter at drier stations, whereas canopy and stomatal parameters become more important where soil moisture is less limiting. Physiological drought also depends strongly on root zone properties, while canopy structure only matters at the drier sites. Stomatal sensitivity to dry air substantially contributed to drought stress at the more humid sites. Highlights: Sensitivity of a forest water balance model to surface/soil parameters was assessed. Varying parameters within plausible ranges may affect water yield by several hundreds of mm/year. Parameter effects and interactions differ between different locations. Drought stress depends on root zone storage capacity and soil absorption capacity. Stomatal closure due to dry air should be considered when modeling drought stress.